Otimização da produção do processo de dobra em uma dobradeira de setup automático - Cunha, Anya Caroliny da (2024)
This study investigates the application of Lean Manufacturing principles and Overall Equipment Effectiveness (OEE) metrics in the bending process of an automatic setup press brake, model DB Amada HG 1003 ATC, within a factory producing gondolas and check-outs. Initially, the machine's OEE showed a low performance of 48.88%, highlighting the need for a detailed analysis of operations and layout to identify waste and bottlenecks. The PDCA methodology was applied to structure corrective actions, including assigning facilitators to assist operators and implementing a dual-work system aimed at minimizing setup time and avoiding bending incomplete lots. With these changes, the average OEE increased to 81.65%, exceeding initial expectations and proving the effectiveness of the interventions in reducing waste and improving process efficiency. Thus, the study demonstrates that an organized approach and optimized use of human and technical resources can yield significant results in industrial productivity and sustainability.